Thirty-Second Walk Test: Expansion of Normative Data. Issue 1 (January 2018) - Lieberstein, Michael; Weingarten, Goldie; Vialu, Carlo; Itzkowitz, Adina; Doyle, Maura; Covino, Frank; Kaplan, Sandra L.
Abstract : Purpose: To collect 30-second walk test (30sWT) normative data on a large, diverse sample of school children developing typically, ages 5 to 13 years, and describe the influences of gender, body mass index, and path shape on distance walked. Methods: Five physical therapists administered the 30sWT on 1223 children developing typically (boys = 517, girls = 706) from 20 urban schools. Results: Average distances (standard deviation) ranged from 139.1 (20.3) to 163.0 (18.6) ft; children aged 10 years walked the farthest and those aged 5 years the shortest. Distance steadily increased from ages 5 to 10 years, steadily decreased from ages 11 to 13 years; children aged 8, 9, and 10 years had statistical but not functionally meaningful gender differences. Body mass index and path shape had no meaningful effects. Distance and velocities are similar to prior studies. Conclusion: This study updated 30sWT normative values with a large, ethnically diverse, urban sample developing typically. Norms may be useful as part of a comprehensive examination. Abstract : Supplemental Digital Content is Available in the Text.The primary purpose of this study is to describe the normative data for the 30sWT using a large sample of children representing current morphological trends and ethnic diversity of an urban sample, and, secondarily, to examine the influence of gender, body mass index, and path shape.